2020
DOI: 10.20884/1.jm.2020.15.3.601
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Essential Oil from Rosemytle Leaves (Rhodomyrtus tomentosa (Ait.) Hassk)

Abstract: Rosemytle leaves (Rhodomyrtus tomentosa (Ait.) Hassk) have been used by society to treat various diseases related to bacterial infections, such as dysentery and typhoid fever caused by Shigella dysenteriae and Salmonella typhi, respectively. This study aimed to evaluate the antibacterial activity of essential oils from rosemytle leaves against both bacterias. Extraction was performed with a macerating device using n-hexane, ethyl acetate, and ethanol extracts, sequentially. This study used the agar diffusion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Antibacterial properties assays were conducted as previously reported Salni & Marisa, 2020) with slight modifications. The essential oil of the leaves and fruit of A. monopleura was tested for its ability to inhibit the growth of Staphylococcus aureus ATCC 25023 and Escherichia coli ATCC 35218.…”
Section: Antibacterial Properties Testmentioning
confidence: 99%
“…Antibacterial properties assays were conducted as previously reported Salni & Marisa, 2020) with slight modifications. The essential oil of the leaves and fruit of A. monopleura was tested for its ability to inhibit the growth of Staphylococcus aureus ATCC 25023 and Escherichia coli ATCC 35218.…”
Section: Antibacterial Properties Testmentioning
confidence: 99%
“…Research conducted by Salni, et al in the Biology laboratory of the Sriwijaya University Palembang in 2013 showed that Alpinia galanga has antifungal compounds including phenolic compounds, in the form of yellowish white crystals. The compound is an antifungal compound Candida albicans [7].…”
Section: Introductionmentioning
confidence: 99%
“…The MIC values of both N1 and E1 for S. dysenteriae and S. Typhi were the same, namely, 125 μg/mL. Isolate N1 was an essential oil containing menthol (59.60%), caryophyllene (25.77%), and cubenol (14.63%), while isolate E1 was essential oil containing (73.93%), pentanone (8.30%), alpha calacorene (7.58%), and calacorene (3.78%) [6].The application of rose myrtle leaves as traditional medicine needs to be proven for its efficacy and safety. Fraction of n-hexane and ethyl acetate of rose myrtle leaves showed antibacterial activity against Streptococcus mutans (MIC of each fraction was 7.8 g/mL…”
mentioning
confidence: 99%
“…The MIC values of both N1 and E1 for S. dysenteriae and S. Typhi were the same, namely, 125 μg/mL. Isolate N1 was an essential oil containing menthol (59.60%), caryophyllene (25.77%), and cubenol (14.63%), while isolate E1 was essential oil containing (73.93%), pentanone (8.30%), alpha calacorene (7.58%), and calacorene (3.78%) [6].…”
mentioning
confidence: 99%